2008
DOI: 10.1038/ismej.2008.111
|View full text |Cite
|
Sign up to set email alerts
|

Environmental microarray analyses of Antarctic soil microbial communities

Abstract: Antarctic ecosystems are fascinating in their limited trophic complexity, with decomposition and nutrient cycling functions being dominated by microbial activities. Not only are Antarctic habitats exposed to extreme environmental conditions, the Antarctic Peninsula is also experiencing unequalled effects of global warming. Owing to their uniqueness and the potential impact of global warming on these pristine systems, there is considerable interest in determining the structure and function of microbial communit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
90
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(97 citation statements)
references
References 36 publications
6
90
0
1
Order By: Relevance
“…The phyla Acidobacteria, Actinobacteria, Bacteroidetes, Cyanobacteria, Proteobacteria, and Verrucomicrobia are frequently observed, and Proteobacteria makes up a substantial proportion of soil sequences in the region, with frequent representation of the Alpha, Beta, Delta, and Gamma Proteobacteria classes (Yergeau et al 2007b). Microarray analyses have indicated that Actinobacteria, Epsilonproteobacteria, and Verrucomicrobia decreased in relative abundance with increasing latitude, whereas Cyanobacteria representation increased (Yergeau et al 2009) findings that largely corroborated earlier clone-library analyses (Yergeau et al 2007b). Additionally, clone-library analyses have revealed a significant decrease in Acidobacteria representation with increasing latitude (Yergeau et al 2007b).…”
Section: Antarctic Peninsulasupporting
confidence: 70%
See 2 more Smart Citations
“…The phyla Acidobacteria, Actinobacteria, Bacteroidetes, Cyanobacteria, Proteobacteria, and Verrucomicrobia are frequently observed, and Proteobacteria makes up a substantial proportion of soil sequences in the region, with frequent representation of the Alpha, Beta, Delta, and Gamma Proteobacteria classes (Yergeau et al 2007b). Microarray analyses have indicated that Actinobacteria, Epsilonproteobacteria, and Verrucomicrobia decreased in relative abundance with increasing latitude, whereas Cyanobacteria representation increased (Yergeau et al 2009) findings that largely corroborated earlier clone-library analyses (Yergeau et al 2007b). Additionally, clone-library analyses have revealed a significant decrease in Acidobacteria representation with increasing latitude (Yergeau et al 2007b).…”
Section: Antarctic Peninsulasupporting
confidence: 70%
“…Additionally, clone-library analyses have revealed a significant decrease in Acidobacteria representation with increasing latitude (Yergeau et al 2007b). Bacteroidetes, Firmicutes, Cyanobacteria, and Alphaproteobacteria were found to be more abundant relative to other taxa in soils of Fossil Bluff (71°19 0 S) and Coal Nunatak (72°03 0 ) on Alexander Island than at sites on the Falkland Islands, Signy Island, and Anchorage Island (51°76 0 S-67°34 0 S) (Yergeau et al 2009). Several phyla were significantly influenced by soil physicochemical factors, as the proportion of Chloroflexi and Betaproteobacteria were negatively (Yergeau et al 2007b); West Antarctic soil sequences (180) are from a study in the Ellsworth Mountains (Yergeau et al 2007b); Victoria Land soil sequences, a total of 426 clone sequences and 25976 pyrosequencing reads, were included from the McMurdo Dry Valleys, from studies in the Miers Valley Tiao et al 2012), Beacon Valley, Wright Valley, Battleship Promontory , Luther Vale (Niederberger et al 2008), and Bull Pass and Vanda in the Wright Valley ); ornithogenic soil sequences (514) are from Cape Hallett and Cape Bird in the Ross Sea region (Aislabie et al 2009); East Antarctic soil sequences (1396) were included from the Larsmann Hills (Bajerski and Wagner 2013) and Schirmacher Oasis (Shivaji et al 2004); and the Transantarctic Mountain soil sequences (361) were from the Darwin Mountains (Aislabie et al 2013).…”
Section: Antarctic Peninsulamentioning
confidence: 99%
See 1 more Smart Citation
“…Although such larger proportion of Proteobacteria in pyrosequencing-based studies might be a true reflection of the communities analyzed, it might also indicate the existence of a cloning bias or that classification based on small 16S rRNA gene fragments could lead to different taxonomic assignments than classification based on near to full-length sequences, as suggested earlier (Elshahed et al, 2008). Nevertheless, Proteobacteria remains the most abundant soil phylum, regardless of the utilized approach, which aside from PCR-based clone libraries and pyrosequencing has included metagenomics (Liles et al, 2003;Tringe et al, 2005), fluorescent in situ hybridization (Zarda et al, 1997) and microarray analysis (Yergeau et al, 2009).…”
Section: Resultsmentioning
confidence: 99%
“…The Phylochip is a microarray that contains oligonucleotide probes designed based on all environmental sample sequences submitted to the RDP website. These sequences have passed a quality check and are deposited in the Greengenes database, http://greengenes.lbl.gov/cgi-bin/nph-index.cgi (Yergeau et al, 2009). The HITChip is another phylogenetic microarray that specifically contains probes for sequences isolated from the human intestinal tract ).…”
Section: Methods To Analyze the Microbiotamentioning
confidence: 99%